Analisis dan Perancangan Sistem Informasi Manajemen Persediaan Barang pada Advan Service Center Jambi - Amelia, Amelia; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2018)
In this time, Advan Service Center Jambi in processing inventory data is still done by manual, that is by recording onthe stock card. Then it is inserted and inputted into microsoft excel to create a report. The purpose of this study toanalyze and study the problem of inventory management information system at Advan Service Center Jambi andproduce prototype inventory management information system at Advan Service Center Jambi. System design in thisresearch using tools UML (Unified Modeling Languange) like use case, activity diagram, and class diagram. Whilein the manufacture of prototype systems using MySQL tools to design databases and Visual Basic.Net 2008 to designa prototype system. This research produces a prototype inventory information system that can manage inventory datain computerized manner and can present reports of goods needed every day or every month.